CITRA BAITUL MAL DALAM PERSPEKTIF PEDAGANG KOTA LANGSA - Kamal, Safwan (JURNAL EKONOMI DAN BISNIS ISLAM, 2016)
Abstrak.This reserch tried to explore the image of the Baitul Mal among the vendors in Kota Langsa. The discussion would focuse on revealing and intepreting the thought of the vendors who were the Muzakki of the Baitul Mal and the non Muzakki of the Baitul Mal on the image of the Baitul Mal Kota Langsa. The approach was qualitive and Schultz?s method ofphenomenologies analysis which provided a wider space for the phenomenon to tell about it self, that specifically analyse the ?because of motives? and?order to motives?. It was found the positive image of Baitul Mal Kota Langsa among the Muzakki Kota Langsa who percieved that the former had peformed well. The Baitul Mall had successfully carried out socialization program and it was well recieved by the muzakki (pedagang swalayan). It had provided the service which has been accessable for the Muzakki to pay their zakkah effectively. It also provied annual report on the addmittance and distribution of zakkah for the Muzakki to be updated. It was part of the transparancy program. Finally, the Amil (distributors), at present has been well recieved and trusted by the muzakki (Pedagang swalayan) in Kota Langsa as the coordinator and distributor of their Zakat.Kata Kunci : Citra Baitul Mal, Pedagang, Baitul Mal Kota Langsa